Case Studies Discussing the Pathology, Immunogenicity, and Proposed Mechanism of Toxicity of an Inhaled Anti-TGFβ Humanized Fab Antibody in Non-Human Primates and Mice. (February 2021) - Hall, Anthony Peter; Cauvin, Annick; Dudal, Sherri; Raymond, James; Rogerson, Petrina; Jolette, Jacquelin
Treatment of nonhuman primates and mice with a humanized antigen-binding fragment (Fab) antibody (UCBFab) inhibiting transforming growth factor β via daily inhalation for up to 13 weeks resulted in low systemic exposure but high local exposure in the lung. Target engagement was demonstrated by reduced levels of signal transducers, phosphoSMAD and plasminogen activator inhibitor-1 in the bronchoalveolar lavage fluid (BALF). Treatment was associated with a high frequency and titer of antidrug antibodies, indicating high local immunogenicity, and local pathology within the lung and draining lymph nodes. Microscopic changes were characterized by perivascular (PV) and peribronchiolar (PB) mononuclear inflammatory cell (MIC) infiltrates that were principally lymphocytic in nature and mixed inflammatory cell infiltrates and/or inflammation within the alveoli. Immunohistochemical investigation revealed a predominantly CD68-positive macrophage and CD3- and CD8>CD4-positive T-cell response in the alveoli, whereas within the airways, there was a variable mixture of CD3-positive T cells, CD20-positive B cells, and CD68-positive macrophages. Increased cellularity of the draining lymph nodes was also noted, indicating the presence of an immune response to the inhaled test article. Morphologic changes did not progress over time, and all changes partially recovered. Increased leukocytes (principally macrophages) in BALF cytology correlated with the changes seen by histopathology.